Peran OJK dalam Regulasi dan Pengawasan Industri Leasing di Indonesia - Muhammad Rifki; Abdul Samuji; Muhammad Raishal R; Joseph Panjaitan (Universitas 45 Surabaya, 2024)
Data from OJK indicates that the number of leasing companies registered is 200. The growth in financing and working capital investment has reached 32.76 percent and 19.93 percent year-over-year. This indicates a significant increase in financing and investment activities within the leasing sector. This study examines how the Financial Services Authority (OJK) regulates and supervises the leasing industry in Indonesia. The research evaluates current concepts and theories based on existing literature using a case study methodology. The findings indicate that leasing plays a crucial role in supporting business financing, and the financial activities of financing institutions in Indonesia are rapidly increasing. However, as credit increases, the risks of default and claims also rise. Therefore, leasing companies must enhance their risk management, and the role of the government in overseeing and protecting consumers is also crucial.